DISEMINASI INFORMASI LOCAL CONTENT MELALUI PELAYANAN BATUAN KARS DI DPK GUNUNG KIDUL - Anjali, Muhammad; Istiqomah, Zeni (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2021)
DPK Gunungkidul offers local content services in the form of Karst Rocks. Information about the topography of karst rocks needs to be preserved because it represents the Gunung Kidul Region. This study aims to determine how the Karst Rock services and how the information dissemination carried out by the Gunung Kidul DPK to the community. This research method uses a qualitative approach and descriptive methods. Data collection techniques using observation, interviews, and documentation analysis. The results showed that the Karst Rocks in the Gunung Kidul DPK were served closed and placed on special racks. The provision of Karst rocks is compiled from research studies in collaboration with external parties. DPK Gunung Kidul provides information to the public about Karst Rocks through information dissemination activities. The process of disseminating information begins with collecting information from the results of research (scientists/researchers) and channeled through the media directly or indirectly so that it can be accepted by users. This activity is carried out to improve the scientific repertoire for the community and form of preservation of karst rock information.